Culturally Responsive Science Education: Developing and Evaluating Ethnoscience-Integrated Animated Videos for Middle School Learners - Fathul Hasanah; Arda Arda; Siti Rabiatul Adawiyah; Windia Hadi (FKIP Universitas Lampung, 2026)
This study aimed to develop and evaluate a Canva-based animated video integrated with Kaili ethnoscience to support students' conceptual understanding of the human respiratory system in junior high school. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of five sequential stages: analysis, design, development, implementation, and evaluation. The developed media was validated by material and media experts, followed by a limited classroom implementation involving 17 eighth-grade students at MTs Nida'ul Khairaat Pombewe. Data were collected through expert validation questionnaires, student response questionnaires, and conceptual understanding tests administered using a one-group pretest-posttest design. The material expert validation yielded an average score of 96.7%. In comparison, the media expert validation produced an average score of 91.7%, both of which were categorized as Very Good, confirming the high validity and technical quality of the developed media. Student reaction was also very favorable across six dimensions: attractiveness, ease of use, clarity, relevance, engagement, and usefulness, which indicate high practicality and acceptance in the classroom. Effectiveness testing results showed a significant increase in students' conceptual knowledge, with an average N-gain of 0.85 (high category) and a large effect size (Cohen’s d = 2.49). Improvements in learning were observed across all seven conceptual understanding indicators, with the greatest increases in classifying (N-gain=1.000), explaining (N-gain=0.947), and comparing (N-gain=0.917). Such results suggest that providing culturally relevant ethnoscience material to students, together with available digital animation resources, may facilitate significant learning in science by helping abstract physiological ideas relate to students' cultural lives. However, because this study employed a one-group pretest-posttest design without a control group and had a limited sample size, the findings should be interpreted with caution. Future studies using controlled experimental designs with larger and more diverse samples are recommended to further validate the effectiveness of ethnoscience-integrated animated learning media. Keywords: animated video, canva, culturally responsive teaching, conceptual understanding, respiratory system, ethnoscience.